Antihyperlipidemic Activity of Kratom Leaves (Mitragyna speciosa) in Metabolic Syndrome Induced-Rats - Sintia Karina Putri; Yuandani; Pipit Pitriani; Said Haikal Alfajar; Rony Abdi Syahputra (GoAcademica Research & Publishing, 2026)
Obesity and hyperlipidemia are metabolic problems that can trigger various comorbid diseases. Kratom leaves (Mitragyna speciosa) are one of the herbal-based medicines containing alkaloid compounds that have the potential to improve lipid profiles. This study aims to analyze the antihyperlipidemic activity of kratom leaves in vivo and in silico. Extraction of kratom leaves was carried out by maceration using 96% ethanol (1:10 w/v) for 3 days, then concentrated using a rotary evaporator. Compound identification was performed using LC-HRMS. The in vivo study was conducted on rats (n=6 per group) for 14 days, including a negative control, positive control, and three treatment groups with doses of kratom leaf extract of 100, 300, and 500 mg/kg BW. The parameters assessed included body weight, LDL cholesterol, HDL cholesterol, triglycerides, and total cholesterol. The results showed that kratom leaf extract at doses of 100, 300, and 500 mg/kg BW exhibited significant antihyperlipidemic activity compared to the negative control (p<0.05), characterized by reductions in triglyceride, total cholesterol, and LDL levels, as well as an increase in HDL and a decrease in body weight. The 500 mg/kg BW dose showed the best pharmacological effect compared to the 100 mg/kg BW and 300 mg/kg BW doses (p<0.05).